RANCANG BANGUN SISTEM INFORMASI PENYEWAAN RUMAH DI KOTA BANYUWANGI MENGGUNAKAN METODE RESEARCH & DEVELOPMENT BERBASIS WEB - Sugiarto, Markus; Andayaningtyas, Novi; Akbar, Raden Ilham (Universitas Bakti Indonesia, 2024)
The advancement of Information and Communication Technology (ICT) in Indonesia has led to a significant increase in the demand for rental housing, in line with urbanization growth. This research employs the Research and Development (R&D) method to develop an efficient web-based application for house hunting. The objective is to enhance the quality of life by providing a solution to house seekers, enabling them to search for and rent homes efficiently. With this application, house hunters can access information about rental properties without the need for physical visits, saving time and effort. Thus, this research makes a valuable contribution to improving the quality of life for urbanizing communities and addressing the challenges in house hunting.